2009
DOI: 10.1007/s10796-009-9166-z
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative systems development in disaster relief: The impact of multi-level governance

Abstract: Disaster management information systems for international humanitarian relief are developed in contexts involving local, national and inter-governmental organizations together with local and international non-governmental organizations (NGOs). While the multi-organizational nature of disaster response is known to create challenges for information systems development, to date, less attention has been paid to their multi-level nature. This research sheds light on the implications of multi-level governance for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
(58 reference statements)
0
23
0
1
Order By: Relevance
“…In addition, the post-2015 HFA stated the importance of the role of international cooperation in supporting the efforts of national and local authorities, communities, and businesses [164]. The envisaged framework involves vertical relationships and processes in the national domain and horizontal corporations that are linked through international initiatives [165]. Hence, the envisaged framework should be organized in two dimensions, multi-level and multi-organizational.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the post-2015 HFA stated the importance of the role of international cooperation in supporting the efforts of national and local authorities, communities, and businesses [164]. The envisaged framework involves vertical relationships and processes in the national domain and horizontal corporations that are linked through international initiatives [165]. Hence, the envisaged framework should be organized in two dimensions, multi-level and multi-organizational.…”
Section: Discussionmentioning
confidence: 99%
“…As this OCHA staff makes clear, even a rough understanding of the size of the population in need is incredibly difficult to know because of the political context of humanitarian crises. Traditional research on governance of complex informational environments is problematic when it is applied to humanitarian organizations because there is little recognition that multiple organizations must coordinate [33]. Furthermore, researchers have found that in this multiorganization non-profit context, there is much concern about visibility to funders, and competition for resources [17,18,61].…”
Section: Th Challenge: the Difficulty Of Producing Humanitarian Informentioning
confidence: 99%
“…Yet the organizational environment is not simply constituted out of interactions between equally powerful actors; many organizational environments are formally structured with actors in management positions who control priorities, decisions, and access to information and technology King et al, 2007). Distributions of power Maldonado, et al, 2010;Robbin and Day, 2006) and organizational politics are determinant of interests and control within organizations and groups, thereby affecting organizational changes, which are a primary subject of SI concern. Distributions of power Maldonado, et al, 2010;Robbin and Day, 2006) and organizational politics are determinant of interests and control within organizations and groups, thereby affecting organizational changes, which are a primary subject of SI concern.…”
Section: Concepts From the Transformational Periodmentioning
confidence: 99%